Anisotropic magnet particles and their manufacturing method
Patent Information
- Application Number
- JP2022540244
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-07-28
- Filing Date
- 2021-07-21
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2041-07-21
AI Technical Summary
【0013】 本発明の異方性磁石微粒子は、バルク化が可能であり、高特性の永久磁石に好適に用いることができる。本発明の異方性磁石微粒子の製造方法によれば、磁化容易方向が一方向であるSm系ハード磁性化合物内に高磁化を有するソフト磁性相を包含する異方性磁石微粒子を得ることができる。
Smart Images

Figure 0007636005000003 
Figure 0007636005000004 
Figure 0007636005000005
Abstract
Description
[Technical field]
[0001] The present invention relates to anisotropic magnetic fine particles suitable for use in high-performance permanent magnets that can be used in a wide range of fields, including electronics, information and communications, medicine, machine tools, and industrial and automotive motors, and a method for producing the same. [Background technology]
[0002] The magnetic compound currently used in the highest performance magnets is NdFe 14 This is a B compound. It is the main phase of the Nd-Fe-B magnet invented in 1982, its crystal structure was determined in 1984, and it is currently used as the strongest permanent magnet material.
[0003] On the other hand, the main phase of NdFeB magnets is Nd2Fe 14 Although compounds with a potential exceeding B have been reported (Non-Patent Document 1, Non-Patent Document 2, Patent Document 1), there have been no reports of successful production of anisotropic bulk magnets, and the performance expected from that potential has yet to be demonstrated.
[0004] Non-Patent Document 3 proposes a nanocomposite magnet composed of a strongly exchange-coupled soft magnetic phase with high saturation magnetic flux density and a hard magnetic phase with high crystalline anisotropy. In principle, this should be superior to the hard magnetic phase alone, and even to NdFeB magnets, and research and development into this magnet is currently underway.
[0005] For example, Patent Document 2 describes that nanocomposite magnets have properties that exceed those of the hard magnetic phase (SmCo5) alone. Non-Patent Document 4 describes an anisotropic nanocomposite magnet that has properties that exceed those of NdFeB magnets.
[0006] Furthermore, Non-Patent Document 5 describes that by adopting a structure in which a soft magnetic phase is contained within a hard magnetic phase whose easy magnetization direction is in one direction, it is possible to exhibit coercivity even if the soft magnetic phase is about 200 nm in size. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 06547141 [Patent Document 2] JP 2006-173210 A [Non-patent literature]
[0008] [Non-Patent Document 1] S. Sakurada et al., Journal of Applied physics, 79 (1996) 4611. [Non-Patent Document 2] Y. Hirayama et al., ScriptaMaterialia 95(2015)70. [Non-Patent Document 3] EFKneller and R. Hawig, IEEE Tran. Magn. 27, 3588 (1991) [Non-Patent Document 4] Wei-Bin Cui et al.,Advanced Materials 24(2012)6530 [Non-Patent Document 5] H. Sepehri-Amin et al., Acta. Materialia 175(2019)276 Summary of the Invention [Problem to be solved by the invention]
[0009] However, the anisotropic nanocomposite magnets in Patent Document 2 and Non-Patent Document 4 have both been realized only in thin films, and bulk magnets have not been achieved. To realize a bulk nanocomposite magnet, it is necessary to reduce the crystal grain size in order to increase the interface area in order to obtain strong exchange coupling, but the powder obtained in currently reported synthesis processes is characterized by being isotropic, making it difficult to realize an anisotropic nanocomposite magnet.
[0010] On the other hand, in Non-Patent Document 5, they succeeded in producing anisotropic nanocomposite powder, but Nd2Fe 14 It is produced using a process that can only be applied to material B. Therefore, at present, it is not possible to produce anisotropic nanocomposite powder (anisotropic magnetic particles) that is the raw material for high-performance anisotropic nanocomposite magnets, in which the soft magnetic phase is well dispersed in the hard magnetic phase (especially in SmCo-based or SmFeN-based materials with high anisotropic magnetic field) in which the easy magnetization direction is in one direction, which is the raw material for high-performance anisotropic nanocomposite magnets.
[0011] The present invention has been made in consideration of the above circumstances, and has as its object to provide anisotropic magnet fine particles that can be made into bulk and contain a soft magnetic phase with high magnetization in an Sm-based hard magnetic compound having one easy direction of magnetization, and a method for producing the same. [Means for solving the problem]
[0012] In order to solve the above problems, the anisotropic magnetic fine particles and the method for producing the same of the present invention are characterized as follows. <1> Anisotropic magnetic particles having a particle diameter of 30 to 500 nm, in which a core is enclosed within a shell, The shell is made of SmCo, which has one easy magnetization direction. x The compound (5.0≦x≦10.0) is characterized in that the core is Co. <2> Anisotropic magnetic particles having a particle diameter of 30 to 500 nm, in which a core is enclosed within a shell, The shell is made of SmFe x N y The compound is characterized in that the core is Fe, and the compound has a structure in which 7.0≦x≦10.0 and 1.0≦y≦2.0. <3> The above <1> A method for producing anisotropic magnet particles, comprising the steps of: A gasification process in which the temperature of the raw material powder containing Sm and Co as the main raw materials is raised to the boiling point or higher to convert it into a gas phase; and A cooling step of cooling the gas phase to 200° C. or less. The present invention is characterized in that it includes: <4> The above <2> A method for producing anisotropic magnet particles, comprising the steps of: A gasification process in which the temperature of the raw material powder containing Sm and Fe as the main raw materials is raised above the boiling point to turn it into a gas phase; The gas phase is cooled to 200° C. or less to form a shell of SmFe x a cooling step to obtain fine particles of the compound, the core of which is Fe; and A nitrogen introduction step in which nitrogen is diffused into the fine particles at a temperature in the range of 200° C. to 600° C. to cause nitrogen atoms to penetrate into the shell. The present invention is characterized in that it includes: Effect of the Invention
[0013] The anisotropic magnetic particles of the present invention can be made into bulk particles and are suitable for use in high performance permanent magnets. The method for producing anisotropic magnetic particles of the present invention makes it possible to obtain anisotropic magnetic particles that contain a soft magnetic phase with high magnetization in an Sm-based hard magnetic compound with one easy magnetization direction. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a schematic diagram of a thermal plasma system used in the examples. [Diagram 2] FIG. 1 shows the results of XRD of a Co-encapsulating SmCox compound. [Diagram 3] (A) is a high-angle annular dark-field (HAADF)-STEM (scanning transmission electron microscope) image of a SmCox particle containing Co, and (B) and (C) are EDX (energy dispersive X-ray) images of Sm and Co, respectively. [Figure 4] FIG. 1 shows HAADF-STEM images (upper row) of SmCox particles encapsulating Co and their Fast Fourier transform (FFT) images (lower row). [Diagram 5]1A and 1B are diagrams showing the results of magnetization measurement of a Co-encapsulated SmCox compound. [Figure 6] FIG. 1 shows XRD results of an SmFex compound containing Fe and an SmFexNy compound containing Fe nitrided in nitrogen at 300° C. and 600° C. [Figure 7] FIG. 1A shows an HAADF-STEM image of an SmFex particle containing Fe, and FIG. 1B and FIG. 1C show EDX images of Sm and Fe, respectively. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] A first embodiment of the anisotropic magnetic fine particles of the present invention will be described. Note that in this specification, when a numerical range is indicated using "to" the numerical range includes both ends of the range.
[0016] The anisotropic magnetic fine particles of the present invention are fine particles having a structure in which a core is enclosed within a shell (core-shell structure), and have a particle diameter of 30 to 500 nm.
[0017] Here, "anisotropy" refers to the magnetic property of a magnetic material being easily magnetized in a specific crystal axis direction, and that direction is one direction. This anisotropy is necessary for a permanent magnet material to have high energy.
[0018] In one embodiment of the anisotropic magnet particles of the present invention, the shell is made of SmCo x The compound (5.0≦x≦10.0) has a Co core.
[0019] The "core-shell structure" of anisotropic magnetic particles can be confirmed by observing with energy dispersive X-ray spectroscopy (EDX) using a scanning microscope or a device attached to a transmission electron microscope. Specifically, EDX measurement is used to confirm that the composition is within a specified range.
[0020] In the present invention, "the easy magnetization direction is unidirectional" means that the direction of the easy magnetization axis is within 2° relative to the particle, regardless of the position of the particle. However, since it is difficult to completely prevent oxidation of the particle surface, even if an oxide layer is present on the particle surface, the target particle can be determined to be a particle with an easy magnetization direction in one direction. The easy magnetization axis is, for example, the axial direction of SmCo5 or Sm2Fe 17 All of N3 are c-axes.
[0021] Furthermore, "the direction of easy magnetization being one direction" can be confirmed by electron beam diffraction using a transmission electron microscope or by direct observation of atoms in high-resolution transmission electron microscope images.
[0022] The shell thickness (Rs) can be exemplified in the range of 5 to 245 nm, and the core radius (Rc) can be exemplified in the range of 5 to 245 nm. The particle diameter of the anisotropic magnetic microparticles having a core-shell structure can be expressed as (2Rs+2Rc), and the particle diameter is 30 to 500 nm. The particle diameter of the anisotropic magnetic microparticles is the maximum length of a straight line that can be drawn in an image when a three-dimensional microparticle is projected two-dimensionally using a transmission electron microscope, a high-resolution transmission electron microscope image, a scanning transmission electron microscope image, or the like.
[0023] The volume fraction of the core is, for example, in the range of 0.08 to 94%, and is more preferably 10 to 25%.
[0024] In addition to the above elements, the anisotropic magnet particles of the present invention may contain unavoidable impurities such as Na, Al, Mn, V, Cr, Ni, Cu, La, Pr, Hf, and Mo as trace impurities of 0.0 to 1.0 at % or less.
[0025] Next, one embodiment of a method for producing anisotropic magnetic particles will be described. The method for producing anisotropic magnetic particles of the first embodiment includes the following steps: A gasification process in which the temperature of the raw material powder containing Sm and Co as the main raw materials is raised to the boiling point or higher to convert it into a gas phase; and A cooling step of cooling the gas phase to 200° C. or less. Includes.
[0026] In the gas phase process, the temperature of the raw material powder (e.g., mixed powder or alloy powder) containing Sm and Co as main raw materials is raised to a temperature above the boiling point to put all the constituent elements into the gas phase. The raw material powder may be a hydride of the above metals.
[0027] The ratio of Sm to Co is, for example, in the range of 1:5 to 1:10, preferably 1:5 to 1:9, in terms of atomic ratio.
[0028] Specifically, the raw material powder can be evaporated by heating, for example, to 1794° C. to 10000° C., preferably 2870° C. to 10000° C. The heating method is not particularly limited, but examples thereof include an RF thermal plasma method, a direct current arc discharge method, and an arc plasma method.
[0029] In the cooling process, the gas phase (gasified raw material powder) is cooled to 200°C or less, and finally to room temperature (e.g., 20°C). Specifically, the temperature can be lowered to room temperature in an inert gas atmosphere, for example, an argon or helium atmosphere. This causes the shell to become SmCo x It is possible to obtain anisotropic magnetic fine particles (powdered fine particles) having a particle diameter of 30 to 500 nm, which is a compound (5.0≦x≦10.0) and has a core of Co. The fine particles can be collected in an inert gas atmosphere, for example, in an argon or helium atmosphere with an oxygen concentration of 100 ppm or less, preferably an oxygen concentration of 10 ppm.
[0030] A second embodiment of the anisotropic magnetic fine particles of the present invention will be described below. Explanations of parts common to the first embodiment will be partially omitted.
[0031] In the anisotropic magnet particles of this embodiment, the shell is made of SmFe x N y The compound has a structure in which 7.0≦x≦10.0 and 1.0≦y≦2.0, and the core is Fe.
[0032] The shell thickness (Rs) can be in the range of 5 to 245 nm, and the core radius (Rc) can be in the range of 5 to 245 nm. The particle diameter (2Rs+2Rc) of the anisotropic magnetic fine particles is 30 to 500 nm. The volume fraction of the core can be in the range of 0.08 to 94%, and is preferably 10 to 25%.
[0033] Next, a method for producing anisotropic magnetic fine particles according to a second embodiment of the present invention will be described.
[0034] The method for producing anisotropic magnet particles of the present invention includes the steps of: a gasification step in which a mixed powder or alloy powder containing Sm and Fe as main raw materials is used as raw material powder, and the temperature of the raw material powder is raised to or above the boiling point to turn the raw material powder into a gas phase; The gas phase is cooled to 200° C. or less to form a shell of SmFe x a cooling step to obtain fine particles of the compound, the core of which is Fe; and A nitrogen introduction step in which nitrogen is diffused into the fine particles at a temperature in the range of 200° C. to 600° C. to cause nitrogen atoms to penetrate into the shell. Includes.
[0035] The vaporization step can be carried out in the same manner as in embodiment 1. The ratio of Sm to Fe is, for example, in an atomic ratio range of 1:7 to 1:10, preferably 1:8.5 to 1:10.
[0036] The cooling step can be performed in the same manner as in the first embodiment. For example, the gas phase can be cooled to 200° C. or less, and finally to room temperature (for example, 20° C.). As a result, the shell is SmFe x It is possible to obtain fine particles having a compound (7.0≦x≦10.0) and an Fe core.
[0037] In the nitrogen introduction step, the obtained SmFe xThe compound can be heat-treated for 10 to 600 minutes at 200 to 600°C, preferably 350 to 450°C, in a nitrogen atmosphere, an ammonia atmosphere, or a mixed gas atmosphere of ammonia and hydrogen or ammonia and nitrogen. This results in a shell of SmFe x N y The compound falls in the range 1.0≦y≦2.0.
[0038] Whether y is in the range of 1.0≦y≦2.0 can be determined from the expansion rate of the unit cell volume calculated from XRD (X-ray diffraction). When the unit cell volume has an expansion rate of 4%-7% based on the volume before nitrogen is introduced, it is determined to be in the range of 1.0≦y≦2.0.
[0039] The anisotropic magnetic particles and the method for producing the same of the present invention are not limited to the above-mentioned embodiments. EXAMPLES
[0040] The anisotropic magnetic fine particles of the present invention and the method for producing the same will be described in detail below with reference to examples; however, the anisotropic magnetic fine particles of the present invention and the method for producing the same are in no way limited to the following examples.
[0041] Example 1: SmCo x Compound preparation and characterization (Raw material powder) The Sm powder was prepared by a known gas atomization method, and then classified with a mesh #500 sieve. The average particle size of Sm was calculated to be 18 μm by laser diffraction. Co powder with an average particle size of 3 μm was purchased from Kojundo Chemical Laboratory.
[0042] The Sm and Co were mixed in an atomic ratio of 1:5, and the mixed powder was used as the raw material powder.
[0043] (Gasification and cooling of raw powder) Figure 1 is a schematic diagram of the thermal plasma system. Using a JEOL TP-40020NPS, an input power of 6 kW and a frequency of 13.56 MHz were applied to the plasma generation coil 102, and thermal plasma was generated in the upper part of the chamber controlled at 100 kPa while flowing G1 grade Ar at 35 L / min. The raw material powder was fed at a feed rate of about 0.3 g / min using a powder feeder 100 (JEOL TP-99010FDR), and the raw material powder was supplied into the generated thermal plasma at about 10,000°C and turned into a gas phase (gas phase generation process).
[0044] Then, in the process of cooling to room temperature below 200° C. near the wall surface of the lower chamber 104, the SmCo alloy, which has one easy magnetization direction as shown in FIG. 3 and FIG. 4, is formed. x Fine particles of 30 to 500 nm having a core-shell structure with Co included therein were obtained (cooling step).
[0045] Thereafter, the powdered fine particles were collected in a glove box 106 at room temperature controlled to an oxygen concentration of about 0.5 ppm and a dew point of −82° C., and the following evaluation was carried out while preventing oxidation as much as possible.
[0046] (XRD) XRD was performed at the Aichi Synchrotron BL5S2 with an incident energy of 14 KeV. The sample was packed into a quartz capillary with a diameter of 300 μm in a glove box and sealed with epoxy resin to prevent oxidation.
[0047] Figure 2 shows SmCo containing Co. x The XRD results of the alloy powder sample after thermal plasma treatment are shown. The hard magnetic phases are SmCo5 and Sm2Co. 17 It can be seen that Co was obtained as the soft magnetic phase.
[0048] (EDX measurement) Figure 3 shows SmCo containing Co. x (A) is a STEM-HAADF image of the alloy particle, and (B) and (C) are EDX images of Sm and Co, respectively.
[0049] From EDX measurements, the atomic ratio of the shell of the particle shown in Figure 3 was Sm:Co = 10.05:89.95, and the core was Sm:Co = 0.01:99.99. A field emission transmission electron microscope ARM (JEOL) was used for observation.
[0050] (STEM-HAADF and FFT images) The STEM-HAADF image (top) and its FFT image (bottom) of the shell portion of an arbitrary microparticle are shown in Figure 4. Similar FFT images were obtained from both the top and bottom of the particle, and it can be seen that the shell portion has a structure in which the c-axis is oriented in one direction, as shown by the arrow in Figure 4.
[0051] (Magnetization measurement) Figure 5(A) shows the initial magnetization curve and demagnetization curve obtained from the magnetization measurement, and Figure 5(B) shows the recoil curve. The springback effect, in which the magnetization returns from a negative magnetic field to zero magnetic field with a positive slope, was observed, and the obtained Co-containing SmCo x It was confirmed that the alloy powder sample was a nanocomposite particle with exchange coupling within each particle.
[0052] (particle size and core volume fraction) The SmCo obtained by transmission electron microscopy x compound (5.0 ≦x≦10. 0) The sizes of 20 arbitrary particles are summarized in Table 1. Here, Rs is the shell thickness and Rc is the core radius. In other words, 2Rs + 2Rc = particle diameter of the microparticle. The volume fraction of the core is (Rc / (Rs + Rc)). 3 This can be calculated by multiplying by 100.
[0053] [Table 1]
[0054] Example 2: SmFe x N y Compound preparation and characterization Sm metal is heat-treated at 500°C in a hydrogen atmosphere to produce SmH 3-- Then, SmH3 crushed to 100 μm or less was mixed with Fe with an average particle size of 3 μm purchased from Kojundo Chemical Laboratory in an atomic ratio of 2:3, and the mixed powder was used as the raw material powder. The gasification process and cooling process of the raw material powder were performed under the same conditions as in Example 1, and the SmFe x Fine particles of 30 to 500 nm in size having a core-shell structure with Fe contained therein were obtained.
[0055] Furthermore, Fe-containing SmFe was subjected to heat treatment at 500°C for 5 minutes in an Ar gas flow. x The sample was heat-treated in an infrared heating furnace under a nitrogen gas flow of 1 L / min at 300 and 600° C., by holding each temperature for 15 minutes (nitrogen introduction step).
[0056] As in Example 1, the measurement was performed at Aichi Synchrotron BL5S2 with an energy of 14 keV. The powder was sealed in a quartz capillary with an inner diameter of 300 μm in a glove box, and then the measurement was performed.
[0057] After the nitrogen introduction step, SmFe x A low-angle shift of the peak due to the nitrogen atom was observed, and the volume of all samples expanded by about 6.05±0.5%, which indicates that nitrogen atoms penetrated in the range of 1.0≦y≦2.0, resulting in the formation of SmFe x N y It was confirmed that the compound was obtained (Figure 6). FIG. 7(A) shows SmFe x N y Figures 7(B) and (C) show the STEM-HAADF image of the particles. Figures 7(B) and (C) show the EDX measurement results. From Figures 7(B) and (C), the atomic ratio of one particle was Sm:Fe=10.01:89.99. A transmission electron microscope (JEOL JEM-ARM200CF) was used for the observation.
[0058] The obtained SmFe x N y compound (7The sizes of 20 arbitrary particles (x≦10.0, y≦2.0) are summarized in Table 2. Here, Rs is the shell thickness and Rc is the core radius. In other words, 2Rs + 2Rc = particle diameter of the microparticle.
[0059] [Table 2]
[0060] Although not shown in Table 2, particles of about 500 nm in size were also confirmed in the scanning electron microscope image. This is because Fe and Co have almost the same saturated vapor pressure and surface tension, so after the raw material evaporates, it becomes a gas phase, and during the quenching process, it undergoes almost the same alloy formation process with Sm, resulting in SmCo. x and SmFe x N y It is reasonable that the particle size ranges obtained for are similar. [Industrial Applicability]
[0061] The anisotropic magnetic particles of the present invention are suitable for use in high-performance permanent magnets that are suitable for use in a wide range of fields, including electronics, information and communications, medicine, machine tools, industrial and automotive motors, etc. In recent years, there has been a demand for even higher performance permanent magnets, particularly with the spread of hybrid cars, the realization of electric aircraft, energy conservation in the industrial field, and improved power generation efficiency.
Claims
1. Anisotropic magnetic particles having a particle diameter of 30 to 500 nm, in which a core is enclosed within a shell, The shell is made of SmCo, the easy magnetization direction of which is unidirectional. x The compound (5.0≦x≦10.0), wherein the core is Co; The shell thickness (Rs) is 5 to 245 nm; The radius of the core (Rc) is 5 to 245 nm; The volume fraction of the core is 1.0 to 41.9%; 2. An anisotropic magnetic particle comprising:
2. Anisotropic magnetic particles having a particle diameter of 30 to 500 nm, in which a core is enclosed within a shell, The shell is made of SmFe having one easy magnetization direction. x N y A compound (7.0≦x≦10.0, 1.0≦y≦2.0), wherein the core is Fe; The shell thickness (Rs) is 5 to 245 nm; The radius of the core (Rc) is 5 to 245 nm; The volume fraction of the core is 1.8 to 48.3%; 2. An anisotropic magnetic particle comprising:
3. A method for producing anisotropic magnet microparticles according to claim 1, comprising the steps of: A gasification step of increasing the temperature of the raw material powder containing Sm and Co as main raw materials to a temperature equal to or higher than the boiling point to convert the raw material powder into a gas phase; and A cooling step of cooling the gas phase to 200° C. or less. Including, The atomic ratio of Sm to Co in the vaporization step is 1:5 to 1:
10. A method for producing anisotropic magnetic particles, comprising:
4. A method for producing anisotropic magnet microparticles according to claim 2, comprising the steps of: a gasification step of increasing the temperature of the raw material powder containing Sm and Fe as main raw materials to a boiling point or higher to convert the raw material powder into a gas phase; The gas phase is cooled to 200° C. or less to form a shell of SmFe x a cooling step to obtain microparticles of the compound, the core of which is Fe; and A nitrogen introduction step in which nitrogen is diffused into the fine particles at a temperature in the range of 200° C. to 600° C. to cause nitrogen atoms to penetrate into the shell. Including, The atomic ratio of Sm to Fe in the vaporization step is 1:7 to 1:
10. A method for producing anisotropic magnetic particles, comprising:
Citation Information
Patent Citations
Rapid preparation method of Co / SmCo composite magnetic material with special structure
CN111292910A
JP06547141B
JP1974002719A
Ferromagnetic ultrafine particle and manufacture thereof, and magnetic recording medium and thermo magnetic recording medium
JP1990180003A
Powder for permanent magnet and its manufacture and anisotropic permanent magnet using the powder
JP1998144509A